Avaliação de cairomônios em sinergismo com diodos emissores de luz (leds) na atratividade de flebotomíneos (diptera: psychodidae). - SILVA, Apoliana Araújo Da (2019)
Sand flies are exclusive vectors of the protozoan parasites of the genus Leishmania. These parasites cause leishmaniasis, a group of neglected diseases characterized by different epidemiological and clinical patterns worldwide. LED (light-emitting diode)-based light traps are used as tools for vector monitoring. Some chemical compounds are important insect attractants and are used in a diversity of traps. The main objective of this study was to evaluate the synergistic effect of Light-Emitting Diodes/LEDs (physical attractants) and kairomones (chemical attractants) on the attraction of sand flies to light traps. To test the synergistic effect, five light traps with the respective combination of attractants [incandescent lamp, incandescent lamp+chemical attractant, green LED, green LED+chemical attractant and chemical attractant alone (without light)] were set between 18:00 and 06:00 following a Latin square design (5X5). The experiments were preformed between August 2017 and August 2018. A total of 6,536 sand flies and 16 species were collected. The most frequent species were: Lutzomyia longipalpis (10.38±0.90/43.21%), Micropygomyia goiana (4.11±0.45/17.12%), Evandromyia lenti (3.82±0.34/15.90%), Evandromyia evandroi (2.97±0.28/12.36%), Nyssomyia whitmani (0.97±0.28/4.07%). In the experiments using octenol, LED+octenol attracted 37.23±5.61 per night, followed by LED alone (35.77±5.69), incandescent lamp+ octenol (18.63±3.28), incandescent lamp alone (14.67±2.86) and octenol alone (1.80±0.65). In the experiments using lactic acid, LED + lactic acid attracted 36.83 ± 4.74 followed by LED alone (34.87 ± 4.61), incandescent lamp + lactic acid (22.80 ± 3.19), incandescent lamp alone (12.67 ± 2.03) and lactic acid (0.46 ± 0.13). The use of LEDs, with or without octenol and lactic acid, was superior to the incandescent lamp with or without such chemicals, showing that LEDs are suitable and efficient light sources for monitoring phlebotomine sand flies.